Thyroid Storm with Multiorgan Failure Treated with Plasmapheresis - Ann Miller; Kristi D. Silver (Case Reports in Endocrinology)
Background. Thyroid storm is a severe manifestation of thyrotoxicosis and can present with multiorgan failure. First line treatment of thyroid storm is directed towards decreasing thyroid hormone production and peripheral conversion of T4 to T3, and treating adrenergic symptoms. When medical therapy fails, plasmapheresis is an alternative treatment option. Here we present a patient with thyroid storm and multiorgan failure who was treated with plasmapheresis. Case. A 50-year-old male with a history of hyperthyroidism, hypertension, and congestive heart failure presented to another hospital with fever and altered mentation. He was found to have pneumonia on imaging and was started on antibiotics. He developed shock complicated by atrial fibrillation with rapid ventricular rate which was treated with amiodarone. He was transferred to our hospital for further management. On arrival, TSH was <0.01 mIU/L, free T4 was >7 ng/dL and total T3 was 358 ng/dL. The endocrinology team determined he was in thyroid storm. His medical treatment of thyroid storm was aggressively titrated to maximal therapy. His hospital course was complicated by transaminitis, respiratory failure requiring intubation, shock requiring vasopressor support, kidney failure requiring continuous renal replacement therapy, and heart failure. Despite maximal anti-thyroid therapy, he had not improved clinically and T4 and T3 remained markedly elevated. A 4-day course of plasmapheresis was initiated resulting in marked lowering of T4 and T3 and clinical stability. Conclusion. While current guidelines for plasmapheresis for thyroid storm recommend individualized decision making, no further clarification is provided on who would be a good candidate for the procedure. We present a patient with thyroid storm and multiorgan failure who was treated with plasmapheresis after failing maximal medical therapy. Given the significant improvement seen with plasmapheresis, endocrinologists should consider this mode of treatment earlier in the course of thyroid storm when patients are not improving with medical therapy alone.